Goos-Hänchen shift in cryogenic defect photonic crystals composed of superconductor HgBa2Ca2Cu3O8+δ - Liu, Fangmei; Hu, Haiyang; Zhao, Dong; Liu, Fanghua; Zhao, Miaomiao (PloS one, 2024)
We explore theoretically Goos-Hänchen (GH) shift around the defect mode in superconducting defective photonic crystals (PCs) in cryogenic environment. The defective PCs are constructed by alternating semiconductors and superconductors. A defect mode arises in the photonic bandgap and sensitively depends on environment temperature and hydrostatic pressure. Reflection and transmission coefficient phases make an abruptly jump at the defect mode and giant GH shifts have been achieved around this mode. The maximum GH shift can get as high as 10 3 λ (incident wavelength), which could be modulated by the values of temperature and hydrostatic pressure. This study may be utilized for pressure- or temperature-sensors in cryogenic environment.